Cuidados paliativos ao paciente com HIV/AIDS: uma abordagem bioética. - Vasconcelos, Monica Ferreira de (2013)
INTRODUCTION: Palliative care is the active and total patient whose disease no longer responds to curative treatment, have great importance in the care of patients with chronic, progressive, advanced, degenerative, incurable disease or end stage such Immunodeficiency Syndrome Acquired AIDS. OBJECTIVES: This study was to thread the following objectives: to investigate the understanding of nurses about the goals of palliative care; to identify the ethical observances adopted by nurses in promoting palliative care to patients with HIV / AIDS. METHODOLOGY: This is an exploratory qualitative approach. Regarding the scenario of the research, it was performed in the Clinic of Infectious and Contagious Diseases (DIC) and the Maternal and Child Care Service (NCS-MI), University Hospital Lauro Wanderley (HULW), located in the city of João Pessoa. Participants were eighteen nurses; to enable data collection, we used a form containing questions relevant to the proposed objectives for the research. Data collection occurred from October to December 2012. DISCUSSION AND ANALYSIS OF DATA: The empirical study was analyzed qualitatively using the technique of content analysis, from the following phases: pre-analysis, material exploration, processing of results. The qualitative analysis yielded the following thematic categories: Category I: Purposes of Palliative Care: Improving the quality of life of patients and their families; Category II: Palliative Care targeted to patients with HIV / AIDS: ethical observances. The latter included two sub categories namely: bioethical principles, respect for human dignity, confidentiality and privacy. The results emphasized that the purpose of palliative care, according to the understanding of the nurses involved with the research was to improve the quality of life of patients and their families. It also pointed out that professionals recognize the importance of multidisciplinary and multi-professional team, to promote that type of care. Regarding ace ethical observances adopted by professionals stood out bioethics principles, respect for human dignity, confidentiality and privacy. These were considered of paramount importance to guide their care practice nurse within palliative care targeted to patients with HIV / AIDS. FINAL - It is hoped that this study will then help to subsidize bioethical reflection regarding the practice of palliative care patients with HIV / AIDS. Also contributing to increase the quantum of publications to the scientific community and, especially, for nursing professionals who work in health care. Considering the small number of studies focused on the respective subject in the context of national literature.